On 2-rainbow domination in generalized Petersen graphs. Issue 1 (2nd January 2017) - Wu, Kuo-Hua; Wang, Yue-Li; Hsu, Chiun-Chieh; Shih, Chao-Cheng
ABSTRACT: In this paper, we show that for all except n =2 k +2, where is a generalized Petersen graph and is the 2-rainbow domination number of . We also conjecture that if and only if k =1, or n =2 k +2 for, or, , , , , .